2019
DOI: 10.1177/0284185119878348
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of image quality applying iterative scatter correction for grid-less skeletal radiography in trauma room setting

Abstract: Background Iterative reconstruction is well established for CT. Plain radiography also takes advantage of iterative algorithms to reduce scatter radiation and improve image quality. First applications have been described for bedside chest X-ray. A recent experimental approach also provided proof of principle for skeletal imaging. Purpose To examine clinical applicability of iterative scatter correction for skeletal imaging in the trauma setting. Material and Methods In this retrospective single-center study, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…As a result, subjective contrast was restored, as demonstrated by thoracic radiography in humans 7,19 and animals 10 . A recent study reported the same beneficial effect on bone structure perception in human skeletal radiography, 30 which is consistent with our results. Disruptive scatter radiation occurs when object diameters are greater than 10 cm 13 ; thus, low amounts of scatter radiation are expected.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As a result, subjective contrast was restored, as demonstrated by thoracic radiography in humans 7,19 and animals 10 . A recent study reported the same beneficial effect on bone structure perception in human skeletal radiography, 30 which is consistent with our results. Disruptive scatter radiation occurs when object diameters are greater than 10 cm 13 ; thus, low amounts of scatter radiation are expected.…”
Section: Discussionsupporting
confidence: 93%
“…Disruptive scatter radiation occurs when object diameters are greater than 10 cm 13 ; thus, low amounts of scatter radiation are expected. However, previous studies have found that scatter correction software also shows a positive effect in anatomic regions where low amounts of scatter radiation are expected 30,19 . Physical antiscatter grids are not routinely used in the radiography of equine distal limbs, as they entail a substantial increase in exposure dose, and positioning is time‐consuming.…”
Section: Discussionmentioning
confidence: 99%
“…Hence viewing via medical-grade screen would be necessary to determine radiological value. In the skeletal grid-less study by Lisson et al ( 11 ), a similar scoring methodology within the trauma room setting was adopted but focusing on bone features. Direct comparison with our study is, however, challenging due to the use of a medical-grade viewing screen and visual grading criteria based on visually sharp reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…To analyze whether the population mean of the differences are different from zero, a paired t-test P value was calculated, under the null hypothesis that the mean of the difference is zero ( 26 ). To analyze whether the distribution of scores is different, the statistical analysis follows an analogous approach ( 11 ). The following two measures were used: (i) a Wilcoxon P value was calculated (under the null hypothesis that the distribution of the pairs is symmetric about zero) ( 27 ); and (ii) the area under the visual grading characteristic curve (AUC VGC ) was reported along with a 95% confidence interval (CI), which was calculated using a non-parametric boot strap with 5000 samples ( 28 , 29 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation